(untitled) (Contemporary Journal of Social Science Review, 2025)
A mobile app heavily relies on user data. If an app doesn’t address user inquiries effectively it may struggle to stay competitive in the market. The blame, for this setback lies with the developer. The demand for Android apps is on the rise. This study delves into. Contrasts two database systems. Room Persistence Library. To complement existing research in this area we carried out experiments by setting up both databases and executing queries. We aimed to determine which database is more user-friendly and efficient. This study proves beneficial for developers seeking to make decisions regarding the database for their projects. It offers insights, into how each database operates and responds aiding developers in grasping their functionality and performance levels.